Alpha-protein kinase 3 (ALPK3) truncating variants are a cause of autosomal dominant hypertrophic cardiomyopathy. (15th July 2021) - Lopes, Luis R; Garcia-Hernández, Soledad; Lorenzini, Massimiliano; Futema, Marta; Chumakova, Olga; Zateyshchikov, Dmitry; Isidoro-Garcia, Maria; Villacorta, Eduardo; Escobar-Lopez, Luis; Garcia-Pavia, Pablo; Bilbao, Raquel; Dobarro, David; et al.
Abstract: Aims: The aim of this study was to determine the frequency of heterozygous truncating ALPK3 variants ( ALPK3 tv) in patients with hypertrophic cardiomyopathy (HCM) and confirm their pathogenicity using burden testing in independent cohorts and family co-segregation studies. Methods and results : In a discovery cohort of 770 index patients with HCM, 12 (1.56%) were heterozygous for ALPK3 tv [odds ratio(OR) 16.11, 95% confidence interval (CI) 7.94–30.02, P = 8.05e−11] compared to the Genome Aggregation Database (gnomAD) population. In a validation cohort of 2047 HCM probands, 32 (1.56%) carried heterozygous ALPK3 tv (OR 16.17, 95% CI 10.31–24.87, P < 2.2e−16, compared to gnomAD). Combined logarithm of odds score in seven families with ALPK3 tv was 2.99. In comparison with a cohort of genotyped patients with HCM ( n = 1679) with and without pathogenic sarcomere gene variants (SP+ and SP−), ALPK3 tv carriers had a higher prevalence of apical/concentric patterns of hypertrophy (60%, P < 0.001) and of a short PR interval (10%, P = 0.009). Age at diagnosis and maximum left ventricular wall thickness were similar to SP− and left ventricular systolic impairment (6%) and non-sustained ventricular tachycardia (31%) at baseline similar to SP+. After 5.3 ± 5.7 years, 4 (9%) patients with ALPK3 tv died of heart failure or had cardiac transplantation (log-rank P = 0.012 vs. SP− and P = 0.425 vs. SP+). Imaging and histopathology showed extensive myocardial fibrosis and myocyte vacuolation. Conclusions : Heterozygous ALPK3 tv are pathogenic and segregate with a characteristic HCM phenotype. Graphical Abstract: